THE ROLE AND IMPORTANCE OF MODERN IT TECHNOLOGIES AND ARTIFICIAL INTELLIGENCE IN THE PRODUCTION OF ANTIBIOTIC PHARMACEUTICALS - Atahanov Sanjarbek Anvarovich; Ergashev Muzaffar Ismoiljon og‘li (Bright Mind Publishing, 2025)
This article highlights the role of modern information technologies and artificial intelligence in the production of antibiotic pharmaceuticals. In recent years, the integration of computer technologies, bioinformatics, and artificial intelligence in the pharmaceutical industry has significantly accelerated and simplified antibiotic development processes. Artificial intelligence systems provide wide opportunities in identifying bacterial resistance mechanisms and predicting the structure of potential active compounds, thereby enhancing laboratory research efficiency. The article emphasizes the importance of IT technologies in improving the effectiveness of antibiotic production, reducing costs, and creating new pharmaceutical agents. Additionally, it discusses the application of modern digital tools in the fight against antibiotic resistance. The study also reviews innovative developments based on artificial intelligence that contribute to advances in antibiotic discovery and development.